HAK-HAK NORMATIF PEKERJA PADA PERUSAHAAN PAILIT - Bustomi, Abuyazid (Faculty of Law, University of Palembang, 2019)
Workers have a very important role and position as actors and in national development. Therefore, there must be labor rights stipulated in the laws and regulations in Indonesia which regulate the rights and protection of workers. Protection of workers is intended to guarantee the basic rights of workers while taking into account the development of fair business actors. Normative Rights of Workers whose companies are declared bankrupt are Priority Creditors after fulfilling the rights of separatist creditors, whose payment is carried out by the curator. The Curator's Authority to the Normative Rights of Employees in Bankrupt Companies is to complete all management and repayment of Debtor's assets and debts, including the Normative Rights of workers as stipulated in Law No. 13 of 2003 and Law No. 37 of 2004 concerning Bankruptcy and Delays in the Payments of Debt Payments, that Normative Rights of Workers including Preferred Creditors or Creditors are prioritized.